El éxito de publicar está reflejado en la honestidad - Velásquez Camacho, Leida Yamile (2019)
This article arises from the need we have, as students and professionals, of writing different types of documents –such as essays, articles, thesis, monographs, the systematizing of professional practice, plays and audiovisual production, among others– in a reliable way so that they could be published. This research aims that students and teachers produce reliable writings that could be published in different media, without committing plagiarism; it also seeks informing about the importance of correct quotation in order to turn it into a habit for the production of reliable documents in the Corporación Universitaria Minuto de Dios (UNIMINUTO), since many research works do not even apply for their publication in other media, as magazines or books, because they lack bibliographic citations. In addition, by ensuring an awareness of this problematic, there would avoid possible legal sanctions which could damage both student’s and teacher’s résumé.   DOI: https://doi.org/10.31876/sl.v2i1.35